2016
DOI: 10.5430/jnep.v6n8p52
|View full text |Cite
|
Sign up to set email alerts
|

Student self-confidence with clinical nursing competencies in a high-dose simulation clinical teaching model

Abstract: Objective: This paper describes undergraduate nursing students' assessment of confidence in clinical practice within a model that uses a "high-dose" of clinical simulation to replace 50% of the traditional clinical experience hours in an upper division bachelor's degree program. We assessed changes in self-reported confidence between the middle and end of a two-year nursing curriculum. Design: Longitudinal design. We surveyed undergraduate nursing students to assess their perceived self-confidence in carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Self-efficacy is an important factor in clinical development, and research has shown that an individual's confidence is a predictor of competent performance in new situations. 9 , 12 …”
Section: Hands-on and Practicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy is an important factor in clinical development, and research has shown that an individual's confidence is a predictor of competent performance in new situations. 9 , 12 …”
Section: Hands-on and Practicalmentioning
confidence: 99%
“… 9 , 24 An individual's confidence can be enhanced with simulation training, which leads to increased knowledge and encourages critical thinking. 12 , 25 To promote self-efficacy, nursing educators should support small learning groups with individual feedback and provide multiple opportunities for students to engage in deliberate practice. 9 , 12 …”
Section: Simulation and Deliberate Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde öğrencilerin simülasyon eğitiminin kişilerarası iletişim becerileri üzerine olumlu etkileri bulunduğu rapor edilen çalışmalar bulunmaktadır. 17,24,25 Bizim çalışmamızda öğrencilerin yalnızca yarıya yakını iletişim becerileri üzerine olumlu etkisi olduğu görüşündedir. Lee ve Kim'in çalışmasında kadın sağlığı hemşireliği simülasyon eğitiminin öğrencilerin iletişim becerilerini geliştirmede etkili olduğu bildirilmiştir.…”
Section: Introductionunclassified
“…'nın çalışmasında ise simülasyon eğitiminin kişilerarası iletişim becerilerini ve işbirliğini artırdığı görülmüştür. 25 Simülasyon eğitimiyle öğrenciler klinik uygulama öncesi hastayla ve ekiple olan iletişim becerilerini her senaryoda öğretim elemanları gözetiminde geliştirmeye çalışmaktadır. Bu nedenle senaryolar eşliğinde simülasyon eğitiminde tekrarlı olarak yapılan iletişim provalarının öğrencilerin iletişim becerilerini geliştirdiği düşünülmektedir.…”
Section: Introductionunclassified